Age-Dependent Changes of Monocarboxylate Transporter 8 Availability in the Postnatal Murine Retina - Henning, Yoshiyuki; Szafranski, Karol (Frontiers in Cellular Neuroscience, 2016)
The thyroid hormones (TH) triiodothyronine (T3) and its prohormone thyroxine (T4) are crucial for retinal development and function, and increasing evidence points at TH dysregulation as a cause for retinal degenerative diseases. Thus, precise regulation of retinal TH supply is required for proper retinal function, but knowledge on these mechanisms is still fragmentary. Several transmembrane transporters have been described as key regulators of TH availability in target tissues of which the monocarboxylate transporter 8 (MCT8), a high affinity transporter for T4 and T3, plays an essential role in the central nervous system. Moreover, in the embryonic chicken retina, MCT8 is highly expressed, but the postnatal availability of MCT8 in the mammalian retina was not reported to date. In the present study, spatiotemporal retinal MCT8 availability was examined in mice of different age. For this purpose, we quantified expression levels of Mct8 via Real-Time Reverse-Transcriptase PCR in mouse eyecups (C57BL/6) of juvenile and adult age groups. Additionally, age-dependent MCT8 protein levels were quantified via Western blotting and localized via immunofluorescence confocal microscopy. While no difference in Mct8 expression levels could be detected between age groups, MCT8 protein levels in juvenile animals were about two times higher than in adult animals based on Western blot analyses. Immunohistochemical analyses showed that MCT8 immunoreactivity in the eyecup was restricted to the retina and the retinal pigment epithelium. In juvenile mice, MCT8 was broadly observed along the apical membrane of the retinal pigment epithelium, tightly surrounding photoreceptor outer segments. Distinct immunopositive staining was also detected in the inner nuclear layer and the ganglion cell layer. However, in adult specimens, immunoreactivity visibly declined in all layers, which was in line with Western blot analyses. Since MCT8 was abundantly present in juvenile and about two-fold lower in adult retinae, our findings suggest a pivotal role of MCT8 especially during postnatal maturation. The present study provides novel insights into age-dependent retinal TH supply, which might help to understand different aspects regarding retinal development, function, and disorders.